Relationship Between Filipino ESL Learners’ Vocabulary Learning Strategies and Vocabulary Ability - Solitana, Jennifer Eve A.; Generoso, Joan C. (Silliman Journal, 2022)
This study focuses on the relationship between vocabulary learning strategies (VLS) as perceived to be used by the ESL learners and their vocabulary ability. The assumption is that learners can build their vocabulary of the target language by applying certain vocabulary learning strategies. The study has recognized learning habits of lexis acquisition among Filipino learners through their perceived use of VLS. Participants of this study were forty students enrolled in freshman English in the university level. Findings revealed no significant relationship between the learners’ vocabulary ability and their perceived use of VLS. This supports the notion that both intentional and incidental vocabulary learning are critical in acquiring vocabulary, accentuating that there is no absolute way for learning vocabulary since it depends upon many varying factors (de Groot, 2006; Brown, 1987). Thus, it is prudent that different approaches of vocabulary instruction be applied in different stages in the language acquisition as with the different contexts in vocabulary learning (Schmitt, 2008). As exhibited by the chosen group in this current study, learners who aim to expand their vocabulary knowledge could increase their acquisition of the target language from the habit of using certain VLS. While language practitioners continue to argue the best ways to improve vocabulary acquisition in the target language, this study confirms that regular revisiting of the lexis is part of a language course.